Kalaupapa : a collective memory - Law, Anwei Skinsnes (Book collections on Project MUSE., 2012)
Between 1866 and 1969, an estimated 8,000 individuals--at least 90 percent of whom were Native Hawaiians--were sent to Molokai's remote Kalaupapa peninsula because they were believed to have leprosy. Unwilling to accept the loss of their families, homes, and citizenship, these individuals ensured they would be accorded their rightful place in history. They left a powerful testimony of their lives in the form of letters, petitions, music, memoirs, and oral history interviews. Kalaupapa combines more than 200 hours of interviews with archival documents, including over 300 letters and petitions written by the earliest residents translated from Hawaiian. It has long been assumed that those sent to Kalaupapa were unconcerned with the world they were forced to leave behind. The present work shows that residents remained actively interested and involved in life beyond Kalaupapa. They petitioned the Hawaii Legislative Assembly in 1874, seeking justice. They fervently supported Queen Liliuokalani and the Hawaiian Kingdom prior to annexation and contributed to the relief effort in Europe following World War I. In 1997 Kalaupapa residents advocated at the United Nations together with people affected by leprosy from around the world. This book presents at long last the story of Kalaupapa as told by its people.